Genotype frequencies of human neutrophil antigen‐3 in the Chinese Zhuang and Dong populations. (22nd October 2017) - Liao, X.; Li, H.; Jiao, W.; Zhu, C.; Wang, W.; Mo, Z.; Yang, Z.; Zhu, Z.
Summary: Individuals with the human neutrophil antigen (HNA)‐3b/3b type can produce HNA‐3a antibodies, which have been reported to cause severe, sometimes fatal transfusion‐related acute lung injury (TRALI). Our study aimed to determine the genotype frequency of HNA‐3a/3b which will be helpful to estimate the potential risk for forming anti‐HNA‐3a, the clinically relevant antibody linked to TRALI in two different ethnic groups of southern China. Five hundred unrelated and healthy blood donors (284 male, 216 female; 300 Zhuangs, 200 Dongs) from the Guangxi Zhuang Autonomous Region were simultaneously typed for the HNA‐3 allele using a polymerase chain reaction sequence‐based typing (PCR‐SBT) method. Genotype frequencies of HNA‐3a/3a, HNA‐3a/3b and HNA‐3b/3b were 51.7%, 39.7% and 8.6% in the Zhuang population, and 44.0%, 49.0% and 7.0% in the Dong population, respectively. Homozygous HNA‐3b/3b genotype frequency among the Zhuang population (8.6%) was significantly higher than previously reported in African Americans (0.4%), Brazilians (3.6%) and English Caucasians (2.9%) ( p  <   .05). And the HNA‐3b/3b genotype frequency among the Dong population was higher than African Americans (0.4%) ( p  <   .05). This study showed Chinese Zhuang and Dong populations possessed a higher frequency of HNA‐3b/3b genotype, suggesting that they may be at greater risk for developing anti‐HNA‐3a alloantibodies that may cause severe cases of TRALI. A molecular‐based identification of the HNA‐3b/3b genotype in all multiparous female blood donors was suggested to reduce the risk of TRALI following plasma and whole blood allogeneic transfusions.